An investigation of early enteral nutrition provision in major burn patients in Australia and New Zealand. Issue 5 (28th June 2022) - Kurmis, Rochelle; Nicholls, Caroline; Singer, Yvonne; Edgar, Dale W.; Wood, Fiona M.; Gabbe, Belinda J.; Tracy, Lincoln M.
Abstract: Aims: Early enteral nutrition (provided within 24 h of admission) is the optimal form of nutritional support for major burn injuries. The aim of this study was to (i) audit early enteral nutrition practices, (ii) identify characteristics of patients who received early enteral nutrition, and (iii) investigate whether early enteral nutrition was associated with in‐hospital outcomes. Methods: An analysis of prospectively collected data from the Burns Registry of Australia and New Zealand was conducted. Specifically, this study focused on major burns patients (defined as burns affecting more than 20% and 15% total body surface area for adult paediatric patients, respectively) admitted to a specialist burn service between 1 July 2016 and 30 June 2019. Results: Data from 474 major burns patients (88 paediatric patients) revealed 69% received early enteral nutrition. Paediatric patients who received early enteral nutrition were younger than their counterparts who did not receive the same support ( p = 0.04). Adult patients who received early enteral nutrition sustained larger burns ( p < 0.001). Early enteral nutrition was not associated with in‐hospital mortality following major burn injury in adult patients in either unadjusted ( p = 0.77) or confounder‐adjusted ( p = 0.69) analyses . Conclusions: Approximately two‐thirds of patients with major burn injuries received early enteral nutrition. Early enteral nutrition was not associated with in‐hospital mortality following major burn injury. Further research should focus on modifiable reasons why major burns patients do not receive enteral nutrition within 24 h of admission.